2,4-D and glyphosate drift interfere with the growth and initial development of rubber trees - Zoz, André [UNESP]; Hirata, Andréia Cristina Silva; Scaloppi Júnior, Erivaldo José; Borges, Wander Luis Barbosa; de Araújo, Tassila Aparecida Do Nascimento; de Freitas, Rogério Soares (FapUNIFESP (SciELO), 2025)
The herbicides glyphosate and 2,4-D are widely used to control weeds in various crops. The rubber tree crop is exposed to these molecules, which can interfere with its establishment. This study aimed to assess the effects caused by the drift of glyphosate, 2,4-D, and the combination of both, in different proportions corresponding to 0, 4, 8, 16, 32, and 64% of the recommended dose (1,440 and 804 g a·e·ha-1 of glyphosate and 2,4-D, respectively). The characteristic symptoms when 2,4-D was present in the drift began with wilting and shriveling of young leaves and, at the highest doses, quickly progressed to chlorosis, shoot epinasty, and edge necrosis, while mature leaves showed a brown color, culminating in a high rate of fall. The effects of glyphosate were intensified after leaf flushing, which occurred 120 days after its application and resulted in long, narrow, twisted leaves in a spiral shape and deformed shoots. Drift above 32% from the combination of glyphosate and 2,4-D resulted in a high mortality rate, while 16% damaged growth and resulted in the death of some plants. The results indicate that drift from the combination of glyphosate and 2,4-D intensifies the symptoms of phytotoxicity in rubber trees, with drift above 8% being harmful. For the herbicides applied alone, there was full recovery of the plants in the drift of up to 16%, so it is important to avoid the drift of these herbicides in the management of weeds in the rubber tree crop.
Keywords: Hevea brasiliensis; necrosis; phytotoxicity; sprout; tolerance